Classroom applications of the reader-response approach in primary and secondary education : A systematic review (1989–2024) - Momeni, Seyed Mohammad; Aerila, Juli-Anna; Routarinne, Sara (International Association for Research in L1 Education (ARLE), 2026)
Rosenblatt’s reader-response theory, with its emphasis on the reader’s role in co-creating meaning, offers insights for enhancing students’ literary experience. This systematic review examined the implementation of the approach within primary and secondary education, focusing on pedagogical practices, text choices, and benefits of reader-response approach for aesthetic engagement. The analysis of 39 empirical studies (1989-2024) revealed four key practices: literature discussions, free response writing and creative writing, reading modality practices, and teacher read-alouds. These practices all emphasize the role of the aesthetic transaction between text and reader in enhancing the reading experience. The review also identified genres such as realistic fiction, multicultural literature, picture books, graphic novels, Gothic literature, humorous fiction, and historical fiction, that have been used in studies applying Rosenblatt’s theory to enhance aesthetic engagement. These studies explored the potential of such texts to enhance aesthetic engagement, particularly when text choices align with students’ interests and backgrounds. Furthermore, the review found that the reader-response approach promotes several key benefits: fostering personal connections and deeper engagement, enhancing personal and literary understanding, fostering empathy, and promoting identity construction. These findings advocate for a pedagogical shift toward practices that prioritize personal connections, interpretive freedom, and the holistic development of readers.